Pendampingan Penyusunan SOP Persediaan dan Optimalisasi Inventory Management System pada UMKM Mandor Dimsum (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
Mandor Dimsum MSME is a culinary business based on a franchise model that has experienced rapid growth since its establishment in 2024 with 10 branches spread across Pasuruan and surrounding areas. The main problem faced is the management of inventory that has not been standardized, especially during the fasting month when demand increases drastically but the supply of raw materials (chicken) is limited, causing stockouts in several branches. In addition, separate stock records between Microsoft Excel for raw materials and the Kasmini Stok application for finished products have the potential to cause data discrepancies. This community service activity aims to assist in the preparation of Standard Operating Procedures (SOP) for inventory and optimization of inventory management systems at Mandor Dimsum MSME. The implementation method uses a qualitative approach with a case study strategy which includes participatory observation, in-depth interviews, SOP preparation, socialization and assistance, and evaluation of SOP implementation. The results show that the preparation of inventory SOPs covering receiving, storage, stock recording, and goods issuance procedures can improve stock data accuracy, accelerate sales transactions, and help optimize raw material ordering time through the application of Reorder Point. This activity makes a real contribution to improving the operational capacity of Mandor Dimsum MSME and can serve as an assistance model for inventory management for similar MSMEs.